ILK O`RTA ASRLARDA ERON MADANIYATINING O`ZIGA XOSLIGI - Otajonova Gulnoza Karimjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article aims to convey information about the uniqueness of Iranian culture in the early Middle Ages, aspects used in its architecture, religion, literature and art through various sources, literature, scientific research works in foreign languages, and information on social networks in an understandable language to the listener.